Training and development practices and executive retention in a research and development organization - Taib, Anita; Krauss, Steven Eric; Ismail, Ismi Arif (Faculty of Educational Studies, Universiti Putra Malaysia, 2018)
Training and development is one of the Human Resource Development areas that used to help employees develop their personal and organizational skills, knowledge and abilities. By providing opportunities to grow and learn, the employees will know that there is room for advancement in the organization. In this paper, the training and development practices is identified and studied from the executive point of view. Series of in depth interviews are conducted on four executives in a research and development organization in Malaysia. Their experience are explored in order to find out how the training and development practices contribute to their decision to stay in the organization. Result shows that both individual training (analytical skill, soft skill and management skill) and organizational training (soft skill, leadership skill and academic programme) contribute to their decision to stay because it makes them being satisfied, being recognized by others in the industry and improvement in their skill. However, some remain in the organization because they are happy working in the organization, passion of doing research and having good working environment.